Reliability of anthropological measurements in determining vertical dimension of occlusion in Saudi population: A cross sectional study - Narendra Basutkar; Aliaa Mahmoud Borham; Saad Ali AlGhamdi; Elaf Waleed Alderea; Mohammed Mansour AlShammari; Khamrunissa Hussain Sheikh (Elsevier, 2021)
Background: Range of techniques have been described in traditional prosthodontics to establish Vertical dimension of occlusion (VDO). Experienced clinicians agree that there is no one single method, which is universally accepted record VDO precisely and consistently. Many facial and body landmarks have been proposed in the literature correlating to the VDO. Presence of so many methods to determine VDO further leads to confusion in the minds of clinicians. There is always a need for a research to both substantiate the findings in the literature and check reliability of such correlations in local population. Such correlation between the anthropological measurements and VDO would give clinician an evidence based approach to establish VDO during prosthetic rehabilitation. Hence this study was planned to check reliability of various anthropometric measurements in measuring VDO in a cross section of Saudi population. Material and method: Total of 500 subjects selected for the study following an inclusion and exclusion criteria. Anthropological readings such as Index finger, Little finger, Thumb finger, Distance between Inner canthus of left eye to outer canthus of right eye and Outer canthus of the right eye to corner of mouth (rima oris) were recorded using digital Vernier caliper. The data were analyzed statistically. Results: Strong positive correlation was observed between VDO and anthropological landmarks selected in the study. Pearson's correlation test showed VDO in males has strong coefficient correlation with Index finger (r = 0.7341) and in females strong coefficient correlation with Little finger. (r = 0.5827). Conclusion: In Saudi Males, VDO could be correlated to the index finger measurements followed by Thumb finger. In Saudi females subjects, VDO correlated with little finger measurements followed by outer canthus of the eye to corner of the mouth reading. It is always appropriate to use one or more methods to approximate the measurements of VDO initially and then use the other methods to test the appropriateness of the dimensions initially established.